Delivering a school-based immunisation programme and maintaining uptake in the context of the COVID-19 pandemic. (2nd October 2020) - Henty, Neil
Abstract : While school-based immunisation programmes generally show good uptake rates, the current COVID-19 pandemic has an impact on their delivery. Neil Henty looks at some of the new challenges faced by health professionals delivering these programmes and how some teams have adapted to overcome them.